THE CORRECT NAMES OF PARASITES IN HUMAN MALARIA - BELTRAN, ENRIQUE (INSTITUTO DE SALUBRIDAD PUBLICA Y ENFERMEDADES TROPICALES, CD. MEXICO, DF, MEX, 1947)
Rats inoculated intranasally with mixtures of murine and typhus rickettsiae demonstrated more massive infection than when inoculated with classic typhus rickettsiae alone The "lung vaccines" from these rats had higher immunizing value against classic typ
THIN SOLID FILMS
Keywords: CORRECT NAMES, PARASITES, HUMAN MALARIA; MULTIDISCIPLINARIA; VIROLOGIA; PARASITOS